Estudo do potencial antitumoral do extrato hidrolisado da espécie euphorbia tirucalli l. em modelos in vitro em câncer de ovário - Wanzeler, Ranna Batista (2024)
Cancer is a group of diseases characterized by the disordered proliferation of cells, which can be influenced by various factors. Ovarian cancer (OC) is the second most common gynecological neoplasm and the fifth most common cause of cancer-related death in women, primarily due to the asymptomatic growth of tumors. Cancer treatment involves various approaches, such as surgery, chemotherapy, and radiotherapy. However, chemoresistance is a challenge in the treatment of malignant neoplasms, leading to increased research on therapeutic combinations that include natural compounds. One substance that has been gaining attention is euphol, a compound found in the latex of the Euphorbia tirucalli plant. There are reports of its use in folk medicine to treat conditions such as inflammation, asthma, cough, warts, and malignant tumors. Thus, this study aimed to evaluate the antitumor potential of the hydrolyzed extract of Euphorbia tirucalli in vitro models using OC cell lines (A2780, ACRP, and OVCAR-3). Metabolic cell viability (MCV) experiments and IC₅₀ calculations were performed for OVCAR-3, A2780, and ACRP cell lines. Clonogenic assay, cell migration, and cell cycle analysis were performed only with OVCAR-3 cell line. MCV assay results showed that the A2780 and ACRP cell lines were not sensitive to the Euphorbia hydrolyzed extract, while the MCV of OVCAR-3 cell line had a significant decrease. Subsequent assays demonstrated that the hydrolyzed extract interferes with both migration and colony formation, drastically reducing viability. Finally, the cell cycle assay performed by flow cytometry showed that the cells were arrested in the G1 phase, corroborating other studies. Therefore, these results suggest a potential antitumor effect of the hydrolyzed extract of Euphorbia tirucalli.